Genetic Characterization of Staphylococcus aureus From Subclinical Mastitis Cases in Dairy Cows in Rwanda - Ndahetuye, Jean Baptiste; Leijon, Mikael; Båge, Renée; Artursson, Karin; Persson, Ylva (Frontiers in Veterinary Science, 2021)
In this study whole-genome sequencing was done on 25 Staphylococcus aureus isolates from subclinical mastitis in dairy cows in Rwanda and the data were analyzed using core genome multilocus sequence typing (cg-MLST). The isolates group into three main clusters. The largest cluster contains isolates of sequence type (ST) 152 and the closely related ST1633 (6+2 isolates). These STs have previously mainly been encountered in humans. The isolates of the second-largest cluster (5 isolates) belong to ST3575 and has previously been isolated from cows with mastitis in Kenya. The third cluster consists of four isolates of ST97, which is a well-known bovine adapted ST. In addition, isolates of the human-adapted sequence types 1 (2), 20 (2), 5 (1), 101 (1), and 2430 (1) were found. ST1 strains are known to cause subclinical mastitis in dairy cows. Finally, one isolates was of ST3591, a ST also previously isolated from cows with mastitis in Kenya. BlaZ, penicillin resistance genes were found in 84% of the isolates and in all cases corroborated by phenotypic resistance determination. Five (20%) of the isolates carried a tetracycline resistance gene (tet(K) or tetM) and three of these five also displayed phenotypic resistance while two isolates carried a tet-gene yet they were tetracycline susceptible. Seven (28 %) isolates carried the dfrG gene conferring resistance to trimethoprim. Four of these isolates indeed were resistant to trimethoprim while three isolates were sensitive. The str gene conferring resistance to aminoglycosides was found in three isolates, however none of this displayed resistance to gentamycin. Our data revealed a high diversity of the sequence types of S. aureus isolates causing subclinical mastitis in Rwanda. Two major cluster of ST97 and ST3575 are known to be bovine adapted and cause mastitis while the third cluster of ST152 usually have been found in humans and may signifying a recent transmission of these types from human to cows for example from hand milking. The STs were distributed without any geographic correlation. Penicillin resistance the most common type of resistance with a prevalence over 80% but also tetracycline and trimethoprim resistance were displayed by several isolates.